SENI DAN DESAIN SANG PRIMADONA,SENI KRIYA SANG PENYELAMAT - Dharsono Dharsono (Pendhapa, 2012)
When emerging dichotomy in art  around 1970s, people who do art (perupa)  in the tradition, are called the artist, meanwhile  people who do craft (pelaku) are called the craftsman or artisan. Especially painting gain a superior position, because the success of western artists in the seat as part of the painting,  that reflect part of intellectuality,  meanwhile craftsmanship is the only mechanical arts. Therefore, fine art becomes to a  marginalized craft and pure art become into the favorite of the timeFurther development, the emergence of trichotomy of art, design and craft (the 1980s), the more visible and tangible. Craft positions below, even debased or is inferior by fine art or design. Then became the belle of the design.But what is the reality?! ...... When Indonesia’s economic crisis in 1998, the craft is thrown down, craft-hall was thrown into marginal, in reality it is an important role to create jobs and even contributed to significant improvements in the economic wheel moving on layer, Even with the collapse of the capital-intensive, it sparked the birth of entrepreneurs to move the craft-based industries such as in Jepara, Cirebon, Surakarta. Even fine art became the savior. Keywords : art, design, fine art, Futuristic University.